The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41598-017-11894-7
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium effects on DNA and protein metabolism in oyster (Crassostrea gigas) revealed by proteomic analyses

Abstract: Marine molluscs, including oysters, can concentrate high levels of cadmium (Cd) in their soft tissues, but the molecular mechanisms of Cd toxicity remain speculative. In this study, Pacific oysters (Crassostrea gigas) were exposed to Cd for 9 days and their gills were subjected to proteomic analysis, which were further confirmed with transcriptomic analysis. A total of 4,964 proteins was quantified and 515 differentially expressed proteins were identified in response to Cd exposure. Gene Ontology enrichment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(18 citation statements)
references
References 83 publications
1
16
0
Order By: Relevance
“…The fertilization success of F0 was also not affected, as already observed in other invertebrates with similar Cd concentrations [49,50] or in fish [51,52]. In addition, a lack of DNA machinery repair in crustacean sperm cells has been suggested in different studies [37,53] and genotoxic effects of Cd on DNA machinery repair have been recorded [54][55][56][57].…”
Section: Cascading Effects On F1 F2 Reproductive Features and F3 Grosupporting
confidence: 65%
“…The fertilization success of F0 was also not affected, as already observed in other invertebrates with similar Cd concentrations [49,50] or in fish [51,52]. In addition, a lack of DNA machinery repair in crustacean sperm cells has been suggested in different studies [37,53] and genotoxic effects of Cd on DNA machinery repair have been recorded [54][55][56][57].…”
Section: Cascading Effects On F1 F2 Reproductive Features and F3 Grosupporting
confidence: 65%
“…Amino acids serve as the building blocks for proteins, so increased levels may reflect decreased protein biosynthesis, as has indeed been previously reported as a consequence of metal (loid) exposure (Kumar and Banerjee, 2016;Viarengo et al, 1980). Reductions in amino acids may be mechanistically linked with alterations to protein folding (Tamás et al, 2014) or repair capacity (Meng et al, 2017), or with alterations to the activity of various enzymes (Kumar and Banerjee, 2013;Mizrahi and Achituv, 1989). The latter is largely consistent with the overall trends observed in the present study, specifically in terms of a well-established relationship between metal(loid) exposure and increased aspartate amino-transferase (AST) enzymatic activity .…”
Section: Biomarker Discovery and Mechanistic Insightsmentioning
confidence: 80%
“…What is more, the myocardial ischemia-reperfusion (I/R) injury was alleviated by PGI2 via decreased oxidative stress ( Zhong et al., 2019 ), and heart protection by NGR1 was closely related to inhibition of oxidative stress ( Yu et al., 2016 ). It is reported that oxidative stress could be induced by ingestion of excessive Cd ( Meng et al., 2017 ), and oxidative stress was related to Cd-induced toxicity in both in vivo or in vitro studies ( Yu et al., 2008 ). Similarly, our results showed that the activation of major detoxification enzymes POD and SOD and the level of GSH were decreased in the Cd-induced chicken heart.…”
Section: Discussionmentioning
confidence: 99%